2014
DOI: 10.1177/0022034514553815
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Autophagy in Lipopolysaccharide-induced Preodontoblastic Cells

Abstract: Odontoblasts derive from neural crest-derived odontogenic mesenchymal cells, and they are an important barrier of defense for the host. Survival and immunity of odontoblasts play important roles in protecting the dentin-pulp structure. Autophagy can eliminate damaged organelles and recycle cellular components to facilitate cellular homeostasis. Autophagy can be activated with external stressors, such as starvation, hypoxia, and infection. In this study, the role of autophagy in inflamed odontoblasts was explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Odontoblasts play a pivotal role in dental pulp inflammation (Couve, Osorio, & Schmachtenberg, ). The previous studies of our group demonstrated that autophagy was of vital importance for survival and apoptosis of odontoblasts during inflammation (Pei et al, ; Wang, Pei, Chen, & Zhang, ). Autophagy was once considered nonselective; however, recent studies indicate that autophagy may be selective under certain circumstances (Farre & Subramani, ).…”
Section: Introductionmentioning
confidence: 81%
“…Odontoblasts play a pivotal role in dental pulp inflammation (Couve, Osorio, & Schmachtenberg, ). The previous studies of our group demonstrated that autophagy was of vital importance for survival and apoptosis of odontoblasts during inflammation (Pei et al, ; Wang, Pei, Chen, & Zhang, ). Autophagy was once considered nonselective; however, recent studies indicate that autophagy may be selective under certain circumstances (Farre & Subramani, ).…”
Section: Introductionmentioning
confidence: 81%
“…A number of studies have provided evidence of the fine-tuning of Atg12-Atg5 in relation to the intracellular redox state (Mai et al, 2012). Pei et al reported that the levels of Atg12-Atg5 were upregulated in a preodontoblast cell line (mDPC6T cells) after treatment with LPS for 6 h and 12 h but were downregulated after treatment with LPS for 24 h (Pei et al, 2015). …”
Section: Redox Regulation Of Autophagy In Periodontitismentioning
confidence: 99%
“…The autophagy marker LC3 was detected within the odontoblast layer in human caries and pulpitis samples . Pei et al showed that LPSinduced autophagy played a dual role in the pre-odontoblast cell line mDPC6T (Pei et al, 2015). The cells could tolerate LPS stimulation, in which autophagy induction by LPS may be an even earlier prosurvival mechanism than the stellar prosurvival molecules Akt and survivin.…”
Section: Dual Role Of Autophagy In Inflamed Odontoblastsmentioning
confidence: 99%